2015
DOI: 10.1136/bmjqs-2014-003921
|View full text |Cite
|
Sign up to set email alerts
|

Impact of laws aimed at healthcare-associated infection reduction: a qualitative study

Abstract: Background Healthcare-associated infections (HAIs) are preventable. Globally, laws aimed at reducing HAIs have been implemented. In the USA, these laws are at the federal and state levels. It is not known whether the state interventions are more effective than the federal incentives alone. Objective The aims of this study were to explore the impact federal and state HAI laws have on state departments of health and hospital stakeholders in the USA and to explore similarities and differences in perceptions acr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(31 citation statements)
references
References 23 publications
1
27
2
Order By: Relevance
“…Without such validation, hospitals that perform more robust surveillance may be unfairly penalized by hospital performance measures linked to these data. At the same time, state and federal laws mandating reporting of healthcare-associated infections have led to increasing collaboration between hospitals and departments of health, 23 along with greater attention from hospital leadership focused on preventing targeted HAIs 24 . Therefore, it is critical that we focus on the benefits of public reporting while understanding and addressing some of the limitations of the publicly reported data.…”
Section: Discussionmentioning
confidence: 99%
“…Without such validation, hospitals that perform more robust surveillance may be unfairly penalized by hospital performance measures linked to these data. At the same time, state and federal laws mandating reporting of healthcare-associated infections have led to increasing collaboration between hospitals and departments of health, 23 along with greater attention from hospital leadership focused on preventing targeted HAIs 24 . Therefore, it is critical that we focus on the benefits of public reporting while understanding and addressing some of the limitations of the publicly reported data.…”
Section: Discussionmentioning
confidence: 99%
“…In most studies, however, consideration of policy implementation was not reported at the point of policy development but was actively performed separate to the directing government body. In some cases, this was undertaken by a coordinating centre or other health system entity or by hospital clinicians themselves as part of the policy implementation and evaluation process (Canaway et al, 2017;Hauschildt et al, 2017;Iorio, 2015;Ketko et al, 2015;Kozhimannil et al, 2013;Nisly et al, 2013;Rejtar et al, 2017;Richards et al, 2008;Shiloach et al, 2010;Smith et al, 2009;Stone et al, 2015;Yelland et al, 2017).…”
Section: Theme 1: Policy Intervention Provides Claritymentioning
confidence: 99%
“…Planning and resourcing Planning for implementation and resourcing of implementation activity was included in policy intervention Canaway et al, 2017;Deasy et al, 2016;Dharampal et al, 2016;Fassl et al, 2012;Hauschildt et al, 2017;Heitmann et al, 2017;Iorio, 2015;Jorgensen et al, 2010;Ketko et al, 2015;Kodal et al, 2012;Kozhimannil et al, 2013;Lambert et al, 2015;Lanese, 2016;Martínez et al, 2009;McClain et al, 2017;Morrow et al, 2012;Nisly et al, 2013;Rejtar et al, 2017;Richards et al, 2008;Russ et al, 2015;Shiloach et al, 2010;Smith et al, 2009;Stone et al, 2015;…”
Section: Claritymentioning
confidence: 99%
See 1 more Smart Citation
“…Although it took decades before the medical community accepted this discovery, infection control practices have changed the practice of medicine, have improved patients' outcomes, and have become the law of the land . For immunocompromised patients, infection control strategies are a fundamental part of modern oncologic care and comprise a multilevel approach, including the patient, the health care environment, the community, and health care workers (Fig.…”
Section: Introductionmentioning
confidence: 99%